2008
DOI: 10.1086/591094
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ex Vivo Evaluation of Long‐Lived Protective Antiviral Memory B Cell Responses against Hepatitis B Virus

Abstract: Our results indicate sustained B cell-mediated protection against HBV despite waning antibody titers, which is consistent with clinical observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…It is well known that a sustained B lymphocytemediated immune response, namely a memory B lymphocyte response, against HBV provides protection against further HBV infection. 22 The present study suggested that loss of memory B lymphocytes in chronic HBV infection may play a role in the persistence of HBV infection and progression to HCC. Alternatively, the abnormalities found in the B lymphocyte subsets might reflect the direct effects of HCC.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is well known that a sustained B lymphocytemediated immune response, namely a memory B lymphocyte response, against HBV provides protection against further HBV infection. 22 The present study suggested that loss of memory B lymphocytes in chronic HBV infection may play a role in the persistence of HBV infection and progression to HCC. Alternatively, the abnormalities found in the B lymphocyte subsets might reflect the direct effects of HCC.…”
Section: Discussionmentioning
confidence: 53%
“…The interaction between HBV and B lymphocytes might be explained by defects in humoral immunity in individuals who develop HCC. 22 Chi et al 23 demonstrated that effective neutralization of HBV might be achieved by low-affinity binding of antibody to nonepitope regions of preS1. Naïve B lymphocytes can be bound to and activated by HBV capsid (core antigen), which stimulates them to become efficient antigenpresenting cells that can prime T lymphocytes and induce an effective immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Memory lymphocyte-mediated protection against infection may persist despite low serum antibody titers, as has been shown for the hepatitis B vaccine. 14 In the current study, monovalent HPV-16 vaccine recipients who were cLIA seronegative at the pre-dose 1 visit also mounted a robust immune response following administration of the quadrivalent HPV-6/11/16/18 vaccine. This suggests that, although these women maintained a low immune response over time, they likely did have immune memory lymphocytes capable of providing a robust immune response.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, the level of serum anti-HBsAb was < 10 mIU/mL in 4 of the 13 children who were negative for HBsAg after prophylactic treatment. Although it is controversial whether booster vaccination is required to maintain adequate levels of anti-HBs antibodies [28-30], all of the 4 children were negative for serum HBV DNA. All of these children had levels of anti-HBs antibodies >10 mIU/mL at 1 year after birth.…”
Section: Discussionmentioning
confidence: 99%